Analisis Penggunaan Dana Transfer dalam Mendorong Pendapatan Asli Daerah Pemerintah Daerah Toraja Utara - Ira Bassang; Marchelin; Marinus Ronal (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to analyze the use of transfer funds in encouraging local revenue (PAD) for the North Toraja Regional Government. The data collection procedure in this research is library research and documentation. This research uses ratio analysis of the degree of fiscal decentralization and financial dependency ratio. The research results show that the average ratio of the degree of fiscal decentralization is 4,63% this means that PAD has very poor ability to finance regional development. Meanwhile, the average financial dependency ratio is 90,74% this means that the financial dependency of the North Toraja Regency area is in a very high category.